Programa Ciência sem Fronteiras: proposta de gestão a partir da avaliação de procedimentos e experiências discentes da Universidade Federal do Espírito Santo - Guimarães, Felipe Furtado (2016)
The main objective of this study was to analyze the Science without Borders program (currently Brazil Scientific Mobility Program - BSMP) in the level of undergraduate sandwich degree abroad, under the perspective of students from the Federal University of Espirito Santo (UFES) and their testimonials. The procedures of the program were assessed by UFES’ staff in order to spread knowledge and suggest improvements, in the context of internationalization. The methodology used was qualitative and quantitative. This research was considered descriptive, explanatory and applied, using instruments such as interviews and survey. Content analysis was used to understand the contents of interviews and testimonials from participants of the BSMP program. The sample included undergraduate students who registered in the BSMP program, in the level of undergraduate sandwich degree abroad and who answered the survey of this research. The main problem found was the dispersion of data about these students, making it difficult to manage this program at UFES. From the interviews with staff from UFES, it was possible to create a flow model of procedures that might help with improvements for the management of this program at UFES. From the testimonials of students and the survey, it was possible to identify that the main outcome of the BSMP program for their education was related to cultural and linguistic aspects. The students also compared the home (UFES) and host institutions. The host institution received higher scores in aspects such as: innovation, technologies to support learning, hours for practical activities and infrastructure. The home institution received good scores in aspects such as: methodology of teaching, pedagogical project and hours for theoretical activities. Actions were proposed for improving the operational procedures of the BSMP at UFES, including the development and implementation of a system for controlling data from students, in the stages of application, exchange program abroad and return to home institution. Besides, this research proposes sharing the knowledge acquired by the students during their experience in the BSMP abroad